Keabsahan Sistem Noken Dalam Pemilu Presiden Dan Wakil Presiden Ditinjau Dari Negara Hukum Dan Demokrasi - Ima Rahmayani; Dodi Jaya Wardana (LPPM Universitas Ekasakti Padang, 2023)
The noken or tie system in Papua is the system used in the presidential and vice-presidential election, technically represented by a big man or tribal chief. The validity of the noken system is not in the form of written rules (laws) but only in the form of traditional Papuan beliefs that have been passed down from generation to generation, in other words, unwritten rules. Because noken is believed to be able to bring relations, familiarity, friendship and kinship among Papuans. This research uses a type of normative legal research with the method of approaching laws and legal concepts. In this study it was found that the noken system had implications contrary to a number of legal and theoretical principles in law. As in a constitutional state that adheres to written rules alluding to elections being held on the basis of direct, free, secret and fair principles. Likewise with the theory of democracy in terms of the implementation of elections that want to be held through absolute participation of the people in politics because it is aimed at the common interest. Preservation of culture through the noken tradition is only suitable for use in everyday life as it can be used in solving local customary problems, through deliberations for consensus through intermediaries of big men or tribal chiefs as the noken system was done before.